Maturation and physiological quality of IAC-863 Rangpur lime seeds - Morelli, Marília; de Azevedo, Fernando Alves; da Conceição, Patrícia Marluci; de Souza, Ana Júlia Borim [UNESP] (Lepidus Tecnologia, 2019)
There is a growing demand for high quality seeds to obtain citrus rootstocks. Normative Instruction 48 (MAPA) of September 24, 2013, requires minimum of 50% germination for the marketing of citrus seeds. Harvest season is one of the stages of seed production with great importance to ensure quality, which makes knowing its maturation process an important step. Thus, the objective of this study was to monitor physicochemical changes in IAC-863 Rangpur lime fruits in order to characterize the physiological maturity of seeds, and to define the ideal harvest point in order to obtain seeds with high physiological quality to obtain rootstocks. Physicochemical analysis of fruits (mass loss, color, soluble solids and acidity) and analysis of seeds (water content, germination and emergence) was performed. Higher germination results were observed in seeds obtained from fruits with higher color index and soluble solids content. The storage of IAC-863 Rangpur lime fruits after harvest increases germination rate, especially in mid-season fruits.
Keywords: Citrus; Germination; Rootstock; Vigor